2013
DOI: 10.1370/afm.1476
|View full text |Cite
|
Sign up to set email alerts
|

Spreading a Medical Home Redesign: Effects on Emergency Department Use and Hospital Admissions

Abstract: PURPOSEThe patient-centered medical home (PCMH) is being rapidly deployed in many settings to strengthen US primary care, improve quality, and control costs; however, evidence supporting this transformation is still lacking. We describe the Group Health experience in attempting to replicate the effects on health care use seen in a PCMH prototype clinic via a systemwide spread using Lean as the change strategy. METHODSWe used an interrupted time series analysis with a patient-month unit of analysis over a 4-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…4 Medical home features, such as enhanced patient access, improved scheduling, care provider continuity, and care coordination activities, have been associated with lower rates of avoidable hospitalizations and decreased Emergency Department use. [5][6][7][8] Multiple difficulties in implementing the PCMH model, however, have been documented. The move away from a physician-centric model of care towards one that is truly team-oriented, and the challenges of aligning financial reimbursement with the PCMH's emphasis on proactive prevention, are only two of the model's persistent challenges across diverse primary care practices.…”
Section: Introductionmentioning
confidence: 99%
“…4 Medical home features, such as enhanced patient access, improved scheduling, care provider continuity, and care coordination activities, have been associated with lower rates of avoidable hospitalizations and decreased Emergency Department use. [5][6][7][8] Multiple difficulties in implementing the PCMH model, however, have been documented. The move away from a physician-centric model of care towards one that is truly team-oriented, and the challenges of aligning financial reimbursement with the PCMH's emphasis on proactive prevention, are only two of the model's persistent challenges across diverse primary care practices.…”
Section: Introductionmentioning
confidence: 99%
“…47 Our study fills an important gap in the literature because existing demonstration-project evaluation efforts have focused on system-level cost savings (eg, through fewer emergency department or specialty visits), which have been inconsistently observed. 10,[14][15][16]18,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] For many practices, revenue gains must be observed at the practice level to justify practice-level workforce and time use changes. Another key advantage is that our modeling allows us to compare different reforms in the same practices, unlike demonstration projects for which it is unclear whether differences in outcomes are due to differences in the PCMH funding program itself or preexisting practice differences.…”
Section: Discussionmentioning
confidence: 99%
“…Medical-home initiatives emphasize prevention and post-acute care, and preliminary studies have shown these models to be effective in reducing ED use among Medicaid beneficiaries. 5 The ACA includes an optional program that gives states additional funding to support providers that develop "health homes" for Medicaid beneficiaries with multiple chronic physical conditions or severe mental illness. The program has been adopted by 16 states to date.…”
Section: Reasons For Visiting the Emergency Departmentmentioning
confidence: 99%